Prediction model for tibial plateau fracture combined with meniscus injury - Lv, Hongzhi; Li, Wenjing; Wang, Yan; Chen, Wei; Yan, Xiaoli; Yuwen, Peizhi; Hou, Zhiyong; Wang, Juan; Zhang, Yingze (Frontiers in Surgery, 2023)
Purpose: To investigate a prediction model for tibial plateau fracture combined with meniscal injury. Methods: This retrospective study enrolled patients with tibial plateau fractures who were treated in the Third Hospital of Hebei Medical University from January 1, 2015, to June 30, 2022. Patients from January 2019 to June 2022 were used as the development cohort, and those from January 2015 to December 2018 were used as the validation cohort. Multivariate logistic regression analysis was used to screen the factors influencing meniscal injury, and a clinical prediction model of tibial plateau fracture combined with meniscal injury was constructed in the development cohort. Model performance was measured by examining discrimination (Harrell’s C-index), calibration (calibration plots), and utility (patient stratification into low-vs. high-risk groups). Models were validated internally using bootstrapping and externally by calculating their performance in a validation cohort. Results: Five hundred patients (313 [62.6%] males, 187 [37.4%] females) with a mean age of 47.7±13.8 years were eligible and were divided into development (n=262) and validation (n=238) cohorts. We identified high-energy injuries as a risk factor (OR=1.969, 95%CI 1.131–3.427). Compared with blood type A, patients with blood type B were more likely to experience tibial plateau fracture with meniscus injury (OR=2.967, 95%CI 1.531–5.748), and office work was a protective factor (OR=0.279, 95%CI 0.126–0.618). The C-index of the overall survival model was 0.687 (95% CI, 0.623–0.751). Similar C-indices were obtained for external validation (0.700[0.631–0.768]) and internal validation (0.639 [0.638–0.643]). Both models were adequately calibrated and their predictions correlated with the observed outcomes (P>0.05). The DCA curve showed that the model had the best clinical validity when the threshold probability was 0.40 and 0.82. Conclusions: Patients with blood type B and high-energy injuries are more likely to have meniscal injury. This may help in clinical trial design and individual clinical decision-making.